Complementation of vif-defective human immunodeficiency virus type 1 by primate, but not nonprimate, lentivirus vif genes. - Simon, J H (1995)
The productive infection of many susceptible human cells, including lymphocytes and macrophages derived from peripheral blood, by the pathogenic lentivirus human immunodeficiency virus type 1 requires expression of the virally encoded vif (for virion infectivity factor) gene. Interestingly, this gene appears to have been conserved among all of the lentiviruses of primates and almost all of the lentiviruses of nonprimates. Using T cells constitutively expressing vif genes derived from diverse sources and virus replication assays, we show that the vif gene of a second primate lentivirus, simian immunodeficiency virus from macaques, complements vif-defective human immunodeficiency virus type 1 but that those of three distinct nonprimate lentiviruses do not. Although the molecular basis for Vif function has yet to be defined, the potential implications of this noted restriction of vif complementarity are discussed.